An overview of recent developments in FLUKA PET tools. (October 2018) - Augusto, R.S.; Bauer, J.; Bouhali, O.; Cuccagna, C.; Gianoli, C.; Kozłowska, W.S.; Ortega, P.G.; Tessonnier, T.; Toufique, Y.; Vlachoudis, V.; Parodi, K.; Ferrari, A.
Highlights: FLUKA PETtools : a dedicated FLUKA package for PET simulations. Simulation of hadrontherapy irradiation scenarios, with in-beam PET, is now possible. The higher imaging potential of 11 C and 15 O in in-beam PET is assessed. The tools feature a newly developed embedded MLEM code for image reconstruction. Abstract: The new developments of the FLUKA Positron-Emission-Tomography (PET) tools are detailed. FLUKA is a fully integrated Monte Carlo (MC) particle transport code, used for an extended range of applications, including Medical Physics. Recently, it provided the medical community with dedicated simulation tools for clinical applications, including the PET simulation package. PET is a well-established imaging technique in nuclear medicine, and a promising method for clinical in vivo treatment verification in hadrontherapy. The application of clinically established PET scanners to new irradiation environments such as hadrontherapy requires further experimental and theoretical research to which MC simulations could be applied. The FLUKA PETtools, besides featuring PET scanner models in its library, allow the configuration of new PET prototypes via the FLUKA Graphical User Interface (GUI) Flair . Both the beam time structure and scan time can be specified by the user, reproducing PET acquisitions in time, in a particle therapy scenario. Furthermore, different scoring routines allow the analysis of single and coincident events, and identification of parent isotopes generating annihilation events. Two reconstruction codes are currently supported: the Filtered Back–Projection (FBP) and Maximum–Likelihood Expectation Maximization (MLEM), the latter embedded in the tools. Compatibility with other reconstruction frameworks is also possible. The FLUKA PETtools package has been successfully tested for different detectors and scenarios, including conventional functional PET applications and in beam PET, either using radioactive sources, or simulating hadron beam irradiations. The results obtained so far confirm the FLUKA PETtools suitability to perform PET simulations in R&D environment.